2019
DOI: 10.1101/776427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil-mediated dynamic capillary stalls in ischemic penumbra: persistent traffic jams after reperfusion contribute to injury

Abstract: the study objectives, designed and performed the experiments, acquired, processed and analyzed the data, wrote the manuscript. J.T. set up and optimized the OCT equipment, wrote acquisition codes and processing algorithms. K.K. designed surgical procedures and performed experiments. D.P set up and optimized the laser speckle imaging equipment, S.K wrote data analysis codes, analyzed data. A.C and J.G. set up and optimized two-photon microscope, prepared data analysis codes and performed the experiments. T.V. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…An increased number of stalled segments has been reported in several neurological diseases, such as Alzheimer's disease and stroke 6,11 . Here, we investigated capillary stalling in a model of subcortical vascular dementia (SVaD).…”
Section: Introductionmentioning
confidence: 99%
“…5 Capillary stalling plays a role in aging, stroke, Alzheimer’s disease, polycythemia, and thrombocythemia. 29 While previous studies have shown that capillary stalling is induced by leukocyte plugging, its underlying mechanism needs to be corroborated. 5,10…”
Section: Introductionmentioning
confidence: 99%
“…5 Capillary stalling plays a role in aging, stroke, Alzheimer's disease, polycythemia, and thrombocythemia. [2][3][4][5][6][7][8][9] While previous studies have shown that capillary stalling is induced by leukocyte plugging, its underlying mechanism needs to be corroborated. 5,10 The endothelial glycocalyx (EG), a layer of proteoglycans and glycoproteins on the luminal side of the vessels, plays an important role in the maintenance of proper microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in IS, leukocytes, and specifically neutrophils, may clog the capillaries and disrupt blood flow (Doerschuk et al, 1993). Impeding inflammatory responses and, recently, reducing these neutrophil stalls have been shown to ameliorate injury in animal stroke models (Cuartero et al, 2013;Drieu et al, 2018;Kelly et al, 2018;El Amki et al, 2020;Erdener et al, 2021). For instance, inhibiting CXCR1 and CXCR2 in rat MCAO model, which are among the biomarkers of inflammation, improves behavioral measures, reduces ischemic brain damage, and decreases IL-1β level in the brain (Villa et al, 2007).…”
Section: Post-ischemic Inflammation Exacerbates Stroke Outcomesmentioning
confidence: 99%